Enhancement of data transmission for mobile multi hop relay worldwide interoperability for microwave access network - Ismael Khalifa Ahmed, Fath Elrahman (2012)
Mobile Multi-hop Relay (MMR) Worldwide Interoperability for Microwave Access (WiMAX) uses Non-Transparent Relay Station (NT-RS) to extend the Base Station (BS) coverage and improve the channel quality and throughput of the network. Nevertheless, the use of NT-RS in MMR WiMAX network increases the delay of relaying packets across multiple hops. Transmission Control Protocol (TCP) and Automatic Repeat reQuest (ARQ) are used to achieve the data transmission reliability in the wireless systems. However, the setting of ARQ parameters are optimised for single hop network and it does not consider the Quality of Service (QoS) limits required of WiMAX networks. In addition, the TCP is adapted to deal with the congestion in the wired network without considering the QoS requirements. In order to enhance the performance of data transmission over MMR WiMAX networks, resource management, transmission control and error control mechanisms should be optimised for MMR WiMAX network. Therefore, this research proposes resource management schemes to decrease the delay of relaying the packets across multiple hops scenario. Transmission control mechanism is then proposed to optimise the transmission control for MMR WiMAX network. Lastly, ARQ parameters are optimised to enhance the link utilisation in order to achieve the QoS rates required. The proposed algorithms performances are evaluated through simulation work. The proposed resource management schemes reduce the delay of relaying packets across multiple hops by 33% and 40% for the second and third hops respectively. Therefore, the link layer throughput is enhanced by 35% and 53% and TCP throughput by 30% and 40% for the second and third hops correspondingly. The proposed transmission control scheme reduces the timeout occurrences which increase the resource utilisation up to 90% and hence the TCP throughput is enhanced by 26% to 75% for different hops. In conclusion, the optimised ARQ parameters for MMR WiMAX network reduce the TCP packet loss by 8%, 44% and 64% for the first, second and third hops. Hence, the link layer and TCP performances are improved by 10% to 140% for diverse scenarios.